The voyage out : contemporary Oriya short stories by women - Satpathy, Sumanyu; Satpathy, Sumanyu (Rupantar, 2007)
Kanaka's husband / Bina Devi -- The open window / Binapani Mohanty -- Family fortunes / Shakuntala Panda -- The ketaki grove / Pratibha Ray -- Bonsai / Yashodhara Mishra -- A mother of Kalahandi / Gayatri Sharaf -- Behind the scene / Sarojini Sahoo -- Moonrise / Supriya Panda -- The heroine / Pushpa Mohanty -- The inner voice / Sushmita Bangchi -- The friend / Paramita Satpathy -- The tale of a rainy night / Hiranmayee Mishra